Microclima, umidade do solo, produção e qualidade da uva ‘Syrah’ sob diferentes sistemas de condução e porta-enxertos na safra do segundo semestre de 2015 - Vale, Clara Nívea Costa do (2016)
The Brazilian viticulture currently occupies an area of 81,000 hectares, especially the Rio Grande do Sul and the agricultural hub Petrolina / Juazeiro-BA accounted for 95% of national fine table grapes exports. The cultivation of the vine is influenced by climate, which directly affects the development of culture, the occurrence of pests and diseases, the water needs and the quality of fruit. The objectives of this study were to evaluate the phenological development, soil moisture variations and vine production Syrah under five rootstocks (PE) and two driving systems (SC), and the variation of the microclimate in different systems as conduction and interfere with the quality of the fruit. The experiment was developed in the Trough of experimental field, in Petrolina, PE, during the second cycle of 2015. We used the Syrah, which is one of the main varieties used in the production of red wine in the São Francisco Valley, divided into blocks, subdivided into plots at random in each block were implanted two microclimate stations in the center of the area cultivated in both drive systems to obtain the microclimate data divided into blocks and divided in blocks. Throughout the crop development cycle measurements were performed in all treatments (SC x PE), in relation to the leaf area index (LAI), photosynthetic active radiation below the canopy (PARabx), fraction of photosynthetically active radiation intercepted by the crop canopy (Fpari), soil moisture 0,20 me production and soil moisture at depths from 0.00 to 0.60 me fruit quality, in 4 treatments, results were evaluated statistically by the Tukey test a 5% probability. The results found that most microclimate variables only significant difference in the final stages of development of culture, parameters except for: albedo, ratio Rn / Rg and soil moisture. There was a significant difference when compared to the EP and SC. The maximum values of LAI presented in the SC in lira and the EP 'IAC 313'. fPARi presented the maximum values in the SC in lira and espalier, respectively, in the EP 'IAC 572' and 'IAC 313'. In both SC Fpari the minimum values were presented at the EP 'P1103'. The analysis of soil moisture in depth from 0.00 to 0.20 m, in both drive systems, the PE 'SO4' and 'P1103' showed higher water requirements. Analyzing soil moisture in depth from 0.00 to 0.60 m PE with the highest water requirement was 'P1103'. The lira driving system provided higher yield per plant in all PE, highlighting the 'IAC 313' with averages of 4.26 and 2.95 kg plant-1, in systems lira and espalier, respectively. We conclude that the conduction system in lira stands out in the production presented in great quality values, but the highest water requirements compared to the conduction system in espalier, as the rootstock 'IAC 572' showed great leaf development and smaller production values in the evaluated cycle